認知症を対象としたアミロイドPET における撮像技術と画像解析 - 山本, 泰司; 相田, 一樹; 赤松, 剛; 大西, 章仁; 千田, 道雄; 井狩, 彌彦 (Nippon Hōshasen Gijutsu Gakkai zasshi, 2017)
Brain imaging techniques, such as computed tomography (CT), magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT), and positron emission tomography (PET), can provide essential and objective information for the early and differential diagnosis of dementia. Amyloid PET is especially useful to evaluate the amyloid-β pathological process as a biomarker of Alzheimer’s disease. This article reviews critical points about technical considerations on the scanning and image analysis methods for amyloid PET. Each amyloid PET agent has its own proper administration instructions and recommended uptake time, scan duration, and the method of image display and interpretation. In addition, we have introduced general scanning information, including subject positioning, reconstruction parameters, and quantitative and statistical image analysis. We believe that this article could make amyloid PET a more reliable tool in clinical study and practice.